2004
DOI: 10.1074/jbc.m311440200
|View full text |Cite
|
Sign up to set email alerts
|

The Human Antimicrobial Peptide LL-37 Transfers Extracellular DNA Plasmid to the Nuclear Compartment of Mammalian Cells via Lipid Rafts and Proteoglycan-dependent Endocytosis

Abstract: Antimicrobial peptides, such as LL-37, are found both in nonvertebrates and vertebrates, where they represent important components of innate immunity. Bacterial infections at epithelial surfaces are associated with substantial induction of LL-37 expression, which allows efficient lysis of the invading microbes. Peptide-mediated lysis results in the release of bacterial nucleic acids with potential pathobiological activity in the host. Here, we demonstrate that LL-37 targets extracellular DNA plasmid to the nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
161
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(177 citation statements)
references
References 49 publications
14
161
2
Order By: Relevance
“…Thus, internalization is largely independent of the binding of the peptide to a specific cell surface receptor, although some specificity may be conferred by different subtypes of proteoglycans due to the structure of the complexes [36]. The process of proteoglycan-mediated endocytosis has also been described for LL37 [37] and is in accordance with the fact that LL37 enantiomers or LL37 mutants, which both retain the cationic structure of the peptide but not its specific amino acid sequence, are still able to condense DNA and trigger endosomal TLR9 activation in pDCs (Supporting Information Fig. 3) [24].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, internalization is largely independent of the binding of the peptide to a specific cell surface receptor, although some specificity may be conferred by different subtypes of proteoglycans due to the structure of the complexes [36]. The process of proteoglycan-mediated endocytosis has also been described for LL37 [37] and is in accordance with the fact that LL37 enantiomers or LL37 mutants, which both retain the cationic structure of the peptide but not its specific amino acid sequence, are still able to condense DNA and trigger endosomal TLR9 activation in pDCs (Supporting Information Fig. 3) [24].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings support a model in which P. aeruginosa internalization can infect epithelial cells through more than one pathway (47), including targeting molecules associated with lipid rafts (48,49), such as Lyn (50) and caveolin-2 (51). LL-37's ability to interact with lipid rafts is suggested by its high surface activity (52), the caveolae-independent membrane raft-dependent endocytosis of an LL-37/DNA plasmid complex (53), and LL-37-mediated/raft-dependent LPS internalization (54). Because LL-37 activates multiple plasma receptors, and the cellular mechanical response to agonists depends on the receptor engaged (55), it is also possible that the LL-37-mediated increase in F-actin concentration results in the formation of distinct cytoskeletal networks with mechanical properties that affect bacterial invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicate that several extracellular DNA-binding proteins, such as high-mobility group B 1, anti-microbial peptide LL37 and heparan sulfate proteoglycan, may be important for DNA uptake under physiological conditions. [17][18][19]30 Therefore, we used two DNA-binding peptides, TAT and LL37, to simulate physiological transfection agents, as reported previously. Using the luciferase-expressing plasmid pGL4.17-CMV and two non-phagocytic cell lines, we found that the transfection efficiency of the plasmid significantly increased after a pre-incubation of LL37 or TAT.…”
Section: Resultsmentioning
confidence: 99%
“…30 For CL treatment, 100 mg ml À1 CL was administered in cell culture for 30 min and then removed by phosphate-buffered saline washing. For intracellular DNA analysis, cells were washed with phosphatebuffered saline containing dextran sulfate (100 mg ml À1 ) for three times to remove extracellular DNA.…”
Section: Dna Uptake In Vitromentioning
confidence: 99%